Excess mortality attributable to antimicrobial-resistant bacterial bloodstream infection at a tertiary-care hospital in Indonesia. - Patricia M Tauran; Irawaty Djaharuddin; Uleng Bahrun; Asvin Nurulita; Sudirman Katu; Faisal Muchtar; Ninny Meutia Pelupessy; Raph L Hamers; Niholas P J Day; Mansyur Arif; Direk Limmathurotsakul (Public Library of Science (PLoS), 2022)
The burden of antimicrobial-resistant (AMR) infections in low and middle-income countries (LMICs) is largely unknown. Here, we evaluate attributable mortality of AMR infections in Indonesia. We used routine databases of the microbiology laboratory and hospital admission at Dr. Wahidin Sudirohusodo Hospital, a tertiary-care hospital in South Sulawesi from 2015 to 2018. Of 77,752 hospitalized patients, 8,341 (10.7%) had at least one blood culture taken. Among patients with bacteriologically confirmed bloodstream infections (BSI), the proportions of patients with AMR BSI were 78% (81/104) for third-generation cephalosporin-resistant (3GCR) Escherichia coli, 4% (4/104) for 3GCR plus carbapenem-resistant E. coli, 56% (96/171) for 3GCR Klebsiella pneumoniae, 25% (43/171) for 3GCR plus carbapenem-resistant K. pneumoniae, 51% (124/245) for methicillin-resistant Staphylococcus aureus, 48% (82/171) for carbapenem-resistant Acinetobacter spp., and 19% (13/68) for carbapenem-resistant Pseudomonas aeruginosa. Observed in-hospital mortality of patients with AMR BSI was 49.7% (220/443). Compared with patients with antimicrobial-susceptible BSI and adjusted for potential confounders, the excess mortality attributable to AMR BSI was -0.01 (95% CI: -15.4, 15.4) percentage points. Compared with patients without a BSI with a target pathogen and adjusted for potential confounders, the excess mortality attributable to AMR BSI was 29.7 (95%CI: 26.1, 33.2) percentage points. This suggests that if all the AMR BSI were replaced by no infection, 130 (95%CI: 114, 145) deaths among 443 patients with AMR BSI might have been prevented. In conclusion, the burden of AMR infections in Indonesian hospitals is likely high. Similar large-scale evaluations should be performed across LMICs to inform interventions to mitigate AMR-associated mortality.